Biomaterials in Valvular Heart Diseases - Taghizadeh, Bita; Ghavami, Laleh; Derakhshankhah, Hossein; Zangene, Ehsan; Razmi, Mahdieh; Jaymand, Mehdi; Zarrintaj, Payam; Zarghami, Nosratollah; Jaafari, Mahmoud Reza; Moallem Shahri, Matin; Moghaddasian, Adrineh; Tayebi, Lobat; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Valvular heart disease (VHD) occurs as the result of valvular malfunction, which can greatly reduce patient’s quality of life and if left untreated may lead to death. Different treatment regiments are available for management of this defect, which can be helpful in reducing the symptoms. The global commitment to reduce VHD-related mortality rates has enhanced the need for new therapeutic approaches. During the past decade, development of innovative pharmacological and surgical approaches have dramatically improved the quality of life for VHD patients, yet the search for low cost, more effective, and less invasive approaches is ongoing. The gold standard approach for VHD management is to replace or repair the injured valvular tissue with natural or synthetic biomaterials. Application of these biomaterials for cardiac valve regeneration and repair holds a great promise for treatment of this type of heart disease. The focus of the present review is the current use of different types of biomaterials in treatment of valvular heart diseases.